Poetry and Possibilities in Contemporary Egypt - Badr, Reem (AUC Knowledge Fountain, 2021)
Egyptian colloquial poetry has historically been conceived of, by practitioners and onlookers alike, as a politically committed, subversive, resistant practice. In this thesis I explore how this poetry, with its complex inheritance, inhabits the realities of post-revolutionary Egypt. Throughout the chapters of this work I trace colloquial poetry in its more traditional forms, as well as in its more novel ones like Egyptian rap/trap, as it grapples with the reduced possibilities in the present. As it reflects and spawns a wider disillusionment with and refusal of politics and claims a reinvention of itself as a private practice, the poetry cannot but be entangled in the webs of the moment and its politics. The elusive nature of poetry and the multitude of dualities it spawns between text and performance, the intimate and the public, emotionality and sociality, past and present, mean that it is uniquely positioned to allow us to grasp and comprehend often unexamined facets of life in today’s Egypt and its politics.